Ancient Empires & mighty people - Sanchez, Richard (Edina, MN : Abdo & Daughters, 1994)
Examines the Hispanic cultural influence on the ancient Central and South American civilizations
Includes bibliographical references and index.
9 - 12 years
Keywords: Indians -- Antiquities -- Juvenile literature; America -- Antiquities -- Juvenile literature